Kewenangan Dewan Perwakilan Daerah Dalam Pengawasan Peraturan Daerah - Muhammad Roqib (Jurnal Justiciabelen, 2022)
Regional Representative Council (Dewan Perwakilan Daerah/DPD) is a constitution organ. This one of state institutions is established and empowered by the 1945 Constitution. The existence of the Regional Representative Council is regulated in the provision of Chapter VII Article 22 C and Article 22 D of the 1945 Constitution. The authorities and duties of the Regional Representative Council is regulated in No. 2/2018 of Law about the People’s Consultative Assembly (MPR), the House of Representative (DPR), the Regional Representative Council (DPD), and the Regional People’s Representative Council (DPRD). One of the Regional Representative Council’s authorities in the Law No. 2/2018 is able to monitor and evaluate the regional regulations plan and the regional regulations. However, since the verdict of Constitutional Court No. 137/PUU XIII/2015 and 56/PUU-XIV/2016 about revocation of the government authority (central) to nullify (executive review) the regional regulation, the authority of the Regional Representative Council in monitoring the regional regulations plan and the regional regulations is weakened and not clear. The nullification of the regional regulation(s) is owned by judicial institution only, such as the Supreme Court (MA). In fact, the Regional Representative Council should be as a representative council that can associate those two interests at once, the central government in top down way and regional interest in bottom up way. How does the Regional Representative Council align those two waves of interests at once through the regional regulation(s)? This research uses statute approach, by examining the related laws about law issues which is already analyzed and also uses conceptual approach, which starts from the point of views and developed doctrines in the legal studies. Based on the research results, it was known that the verdict of the Constitutional Court did not eliminate the control of the central government, in this case was the Regional Representative Council to the regional government, including the making of the regency/city regional regulations. But, this control was not in the shape of testing or nullifying the regional regulations. The Regional Representative Council in consort with the ministry, and governor as the representative of the central government should do some evaluation process on each regional regulations plan.